CLINICAL SIGNIFICANCE OF ANTISPERM ANTIBODY ANALYSIS IN EVALUATING MALE INFERTILITY OF SOUTH KARNATAKA - G. SREENIVASA,; P. KAVITHA,; P. T. CHAITHRA,; V. S. VINEETH,; C. SHARAT KUMAR,; S. SUTTUR MALINI, (The Bioscan, 2011)
The presence of anti-sperm antibodies (ASA) in semen or blood serum may impair sperm function leading to immunological infertility. Hence, the clinical significance of anti-sperm antibody (ASA) analysis is gaining momentum. ASA screening was done on 64 patients registered for infertility treatment. Out of 64 patients, 38 (59.3 %) members showed positive response for ASA in their blood serum. Among them maximum number of patients belong to age group between 31-40 years. In this study ejaculatory dysfunction showed 100% positive response for ASA followed by asthenospermic condition (83.33%). Response of oligospermic (57.14%) and azoospermic (47.82%) were in accordance with the other studies. Poor semen parameters were observed, especially the alkaline nature of semen, increased liquefaction time and change in the colour which confirms the infection in the patient. More than 50% of infertile patient of all etiologies showed positive results for the presence of ASA, and the prevalence probably increases with increase in patient’s age.